Penerapan Gaya Kepemimpinan Deleglasi Dan Trasformasi Terhadap Kinerja Kepala Desa (Desa Margorejo, Kecamatan Padang Ratu, Kabupaten Lampung Tengah) - Mulyadi, -; Alansori, Apip; Fahrizal, Azli; Ansah, Andre (Universitas Malahayati, 2025)
Leadership style is a very important tool in an organization, and researchers often study it. This research aims to find out how delegation and transformation leadership styles affect how well the village head does their job. The research data was gathered through questionnaires and observations, with 42 people answering, including community and environmental leaders. The data was analyzed using the SPSS 27 program. The test results showed that the delegation leadership style did not affect the village head's performance, but the transformation leadership style had a big impact